Role of Metformin in Women's Health: Review of Its Current Place in Clinical Practice and Emerging Indications for Future. Issue 5 (May 2016) - Sinai Talaulikar, Vikram; Tang, Thomas; Yasmin, Ephia
Abstract : Importance: Metformin, an oral antihyperglycemic drug, acts as an insulin sensitizer in the treatment of type 2 diabetes mellitus. It has also been widely used in the treatment of polycystic ovary syndrome (PCOS) and gestational diabetes mellitus. Although randomized clinical trials have failed to establish its superiority over other forms of treatment, metformin continues to be a treatment option in specific subgroups of women either alone or as an adjunct with other therapies in management of PCOS. Objective and Evidence Acquisition: This narrative review was conducted to assess the present role of metformin in management of clinical conditions related to women's health. A PubMed search was conducted using the following terms: "metformin, " "polycystic, " "ovary, " "Women's, " "health, " "gestational, " "diabetes, " "cancer, " and "fertility, " and all relevant studies were evaluated for accumulation of evidence. Results and Conclusions: Metformin is used as a second-line drug for ovulation induction in women with PCOS who are resistant to clomiphene citrate. Metformin also forms one of the management options in women who need antiandrogen therapy without the need for contraception at the same time. Women with PCOS undergoing in vitro fertilization are likely to benefit from metformin therapy to reduce their risk of ovarian hyperstimulation syndrome. Metformin alone or in combination with insulin has been reported to have similar safety and efficacy to insulin for the treatment of GDM. There is growing evidence that metformin may be associated with a decreased risk of developing cancers and improved response to chemotherapy. Target Audience: Obstetricians and gynecologists, family physicians Learning Objectives: After completing this CME activity, physicians should be better able to (1) describe the mechanism of action of metformin and common adverse effects associated with its use, (2) counsel women about the role of metformin in induction of ovulation and treatment of hyperandrogenemia in polycystic ovary syndrome, and (3) describe the role of metformin in management of gestational diabetes mellitus.